PERANAN ACADEMIC SELF EFFICACY TERHADAP ACADEMIC BURNOUT PADA PESERTA DIDIK SMA DALAM PERALIHAN PEMBELAJARAN DARING KE PEMBELAJARAN LURING - Vania Rizka Amalia; Rika Vira Zwagery; Rusdi Rusli (Jurnal Education and Development, 2022)
This study aims to investigate whether there is a role of academic self-efficacy on academic burnout in high school students during the transition from online learning to offline learning. The method used in this study was a quantitative correlational survey with a cross sectional research design. The characteristics of the respondents included the high school students who experienced the transition from online learning to offline learning. The sampling technique was thenon-probability sampling with the purposive sampling type. Data were collected through offline and online questionnaires via google form. The measurement instruments consisted of the Morgan-Jinks Student Efficacy Scale (MJSES) and the School Burnout Inventory (SBI) which had gone through the adaptation process according to the stages of Beaton et al. (2000). The respondents in this study were (n=243) from three different high schools in Banjarmasin. The result of hypothesis testing using the simple linear regression analysis showed a significance level of 0.000 (p<0.001) and a regression coefficient b = -0.341. It can be assumed that there is a significant negative role between academic self-efficacy and academic burnout in high school students during the transition from online learning to offline learning. The academic self-efficacy variable had a contribution of 11.6% to academic burnout, and the rest was influenced by other factors.